Small-and medium-enterprises' understanding and preparedness on goods and services tax - Abdul Aziz, Saliza (Universiti Utara Malaysia, 2007)
The main objective of this study is to know GST from the SMEs taxpayers’ perspective, as well as to identify the level of preparation after the announcement of postponing the implementation date.In addition to that, the research also list out the incentives require by the SMEs in adopting and implementing GST successfully.Indeed, there are alternative ways to improve the compliance towards GST among the SMEs taxpayers.In overall, the 107 respondents who are among the SMEs’ Enterprise 50 Award recipients seemed to have a clear idea and picture of the proposed GST.Even though there are most likely prepared to adopt or implement the new system, certain issues of concerns need to be addressed by the relevant authorities.In respect of the incentives require, there are several possible suggestions in terms of software and appropriate GST rate. Most of the respondents perceived that direct communication, i.e. a special website or help line would be more ease than searching for the information or guidance on GST.